Estimates of the Open Economy New Keynesian Phillips Curve for Euro Area Countries - Fabio Rumler (Oesterreichische Nationalbank (OeNB), 2005)
This paper extends the existing literature on the open economy New Keynesian Phillips Curve by incorporating three different factors of production, domestic labor and imported as well as domestically produced intermediate goods, into a general model which nests existing closed economy and open economy models as special cases. The model is then estimated for 9 euro area countries and the euro area aggregate. We find that structural price rigidity is systematically lower in the open economy specification of the model than in the closed economy specification indicating that when firms face more variable input costs they tend to adjust their prices more frequently. However, when the model is estimated in its general specification including also domestic intermediate inputs, price rigidity increases again compared to the open economy specification without domestic intermediate inputs.
Keywords: E31; C22; E12; 330; New Keynesian Phillips Curve; Open Economy; GMM